Quaternized Chitosan-Coated Montmorillonite Interior Antimicrobial Metal-Antibiotic in Situ Coordination Complexation for Mixed Infections of Wounds - Sun, Baohong (Langmuir : the ACS journal of surfaces and colloids, 2019)
Conventional drug delivery systems for natural clay materials still face critical challenges in their practical application, including multiple bacterial infections, combined infection of bacteria and fungi, and low sterilization efficiency. In this work, we address these challenges using the multifunctional montmorillonite nanosheet-based (MMT-based) drug nanoplatform, which involves the antibiotic 5-fluorocytosine (5-FC), antibacterial metal copper ions, and quaternized chitosan (QCS). Composite material QCS/MMT/5-FCCu can can strongly inhibit Staphylococcus aureus (a typical Gram-positive bacterium), Escherichia coli (a typical Gram-negative bacterium), and Candida albicans (a fungus) because 5-FC coordinates with copper ions in situ and due to the deposition of QCS. The subsequent drug release behavior of 5-FCCu was studied, and the results show an initial high concentration kills microorganisms and long-acting sustained release inhibition. Moreover, in vivo wound experiments and toxicity experiments show the promotion of wound healing and excellent biocompatibility. As a demonstration of the utility of the latter, we have shown that the MMT-based smart platform can be used for the treatment of mixed infections of wounds